Bilateral Proatlantal Intersegmental Artery Type I with Vertebrobasilar Stroke: A Rare Case with Successful Angioplasty and Stenting - Shubhamoy Gantait; Vikram Huded; Tanaya Mishra; S Anush Rangarajan; Girish Gadre (Annals of Indian Academy of Neurology)
Proatlantal intersegmental artery (PAIA) is an extremely rare, persistent carotid–vertebral anastomosis and is generally diagnosed by imaging done for other unrelated disorders. We present a case of bilateral type I PAIA, where the patient presented with vertebrobasilar stroke and cerebral catheter angiogram was done as part of the diagnostic protocol. Significant stenosis was found at the distal portion of the left PAIA. It was successfully treated by angioplasty and stenting.